2000
DOI: 10.1046/j.1526-4610.2000.00025.x
|View full text |Cite
|
Sign up to set email alerts
|

Acquired Transient Stuttering During a Migraine Attack

Abstract: Stuttering is an abnormality in the fluency of speech, which is characterized by interruption of the normal rhythm due to involuntary repetition and prolongation, or arrest, of uttered letters or syllables.The aphasic syndrome and dysarthria can be associated with classic migraine, but, to our knowledge, no study has so far described stuttering as the only neurological symptom accompanying an attack.Key words: stuttering, migraine, aphasia ( Headache 2000;40:170-172) CASE HISTORYA 26-year-old, right-handed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2006
2006
2010
2010

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 10 publications
1
10
0
Order By: Relevance
“…For instance, Leder (1996) has described a patient with Parkinson's Disease who showed no specific word fears, no secondary stuttering characteristics, no adaptation effect and who stuttered equally on all types of speech. The patient described by Perino et al (2000) also stuttered during conversational speech and oral reading, had no secondary stuttering characteristics and no specific word fears. In contrast, other case studies have demonstrated that not all patients with neurogenic stuttering may conform to all of the suggested differential characteristics.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…For instance, Leder (1996) has described a patient with Parkinson's Disease who showed no specific word fears, no secondary stuttering characteristics, no adaptation effect and who stuttered equally on all types of speech. The patient described by Perino et al (2000) also stuttered during conversational speech and oral reading, had no secondary stuttering characteristics and no specific word fears. In contrast, other case studies have demonstrated that not all patients with neurogenic stuttering may conform to all of the suggested differential characteristics.…”
Section: Introductionmentioning
confidence: 96%
“…Based on published data, this acquired form of stuttering is most often associated with stroke (Jokel, De Nil, & Sharpe, 2007;Sahin, Krespi, Yilmaz, & Coban, 2005;Van Borsel, Van Der Maede, & Santens, 2003), traumatic brain injury Ludlow, Rosenberg, Salazar, Grafman, & Smutok, 1987;Yeoh, Lind, & Law, 2006), neurodegenerative disease (Koller, 1983;Leder, 1996;Mowrer & Younts, 2001), or another neurological event that affects brain function (Byrne, Byrne, & Zibin, 1993;Movsessian, 2005;Perino, Famularo, & Tarroni, 2000;Tsao, Shad, & Faillace, 2004). Although neurogenic stuttering behaviorally appears to have a lot of similarity to developmental stuttering, a number of authors have suggested several features which may differentiate it from developmental stuttering.…”
Section: Introductionmentioning
confidence: 99%
“…However, we need to consider the possibility that either pain, in itself, could potentially provide the ''trigger'', or that the trauma of the condition could have set up the stress condition that allows the stutter to appear, and then with the chronic nature of the condition, persist. Again though, if we were to accept that this case represents, some kind of ''pain induced'' stutter, it is unclear why, when the pain was controlled, the stutter did not resolve or improve, as reported in both the two cases mentioned earlier (Perino et al, 2000;Ward, 2006).…”
Section: Some Thoughts On Diagnosis and Relevance To Therapymentioning
confidence: 82%
“…There are some anecdotal reports of pain potentially being associated with acquired stuttering. Perino, Famularo, and Taroni (2000) reported transient stuttering in an individual during a migraine attack. Ward (2006) also reported the case of apparent PS in an individual suffering from chronic and intense back pain.…”
Section: Psychogenic Stutteringmentioning
confidence: 99%
“…Aphasic changes occur more frequently (47%), are more severe, and last longer when associated with hemiplegic migraine 6 . The language or speech symptoms occurring during a migraine attack with aura appear to be hard to categorize, 1 but include dysarthria, 1 stuttering, 7 nonfluent or Broca's aphasia, 8,9 and anomia 4 …”
Section: Discussionmentioning
confidence: 99%